Hubungan Konsep Diri Dengan Penyesuaian Diri Pada Pelajaran Peminatan Siswa Kelas XI SMK Bhina Tunas Bhakti Juwana - Dwi Anggreni, Melliana Septi; Suyati, Tri; Setiawan, Agus (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study aims to determine the relationship between self-concept and self-adjustment in specialization lessons for class XI students at Bhina Tunas Bhakti Juwana Vocational High School. This study uses a correlational quantitative research method. The population in this study was 150 students of class XI, then to determine the sample in the study using the cluster random sampling technique, namely determining the sample randomly not individually but all members of the group. In taking this sample, the researcher randomized the five population classes twice. The first class that came out, the researcher used for the try out class, namely class XI TEI 1 and the second class that came out for the research class was class XI TOKR 1. Tools for data collection, researchers used self-concept and self-adjustment scale instruments. Based on the results of the research that the researchers have done, it can be concluded as follows: there is a relationship in the moderate but significant interval class category, and the direction of the relationship is negative. A negative significant relationship means that it means that the relationship is inversely proportional if the self-concept or variable X has increased, the student's self-adjustment or variable Y has decreased, so conversely if the Y variable or student's self-adjustment has increased then the X variable or student's self-concept has decreased. This is shown by the statistical results using the Pearson product moment correlation test with the help of the SPSS 23 application with the result r = (-) 0.42 with an r table of 0.361, so r count > r table or (-) 0.42 > 0.361. Then matched with the interpretation table shows that between self-concept and self-adjustment has a relatively moderate level of relationship.